PENGARUH LATIHAN PUSH-UP DAN BALL-SLAMS TERHADAP KEMAMPUAN SERVICE FLOATING DALAM PERMAINAN BOLA VOLI PADA ATLET CLUB SEMEN PADANG - muhamad sazeli rifki; Okky Satria Putra; Fahd Mukhtarsyaf (Jurnal Sporta Saintika, 2019)
Abstract :The problem in this study is the low ability of service floating in volleyball games at Semen Padang Club Athletes and not yet seen by players in the match. This study aims to determine how much influence the push-up and ball slams exercise has on the ability of floating services in volleyball games in the athletes of Semen Padang club. This type of research is a quasi-experimental study design with one group pre-test and post-test design. The population in this study is athlete volleyball club Semen Padang as many as 45 people. Sampling using purposive sampling technique with a sample of 20 people. The hypothesis proposed in this research is the significant influence of push-up and ball slams exercises on the ability of floatin service in volleyball game at club athlete Semen Padang. The results showed that in the group given push-up training obtained t count value > t table (7.73 > 1.833). This means that the influence of training Push-Up Against the Ability of Service Floating Volleyball Athlete Club Semen Padang. In the group were given ball slam training Tcount > t tabel (11.67 > 1.833). This means that there is an effect of Ball Slam training on the ability to service Floating Semen Padang Volleyball Club Athletes. To see the difference of Push-up practice and Ball Slam training on the ability of Service Floating Volleyball Athlete Club Semen Padang with value tcount > t table (16.68 > 1.833). It can be concluded that there are differences in the practice of Push-ups and Ball Slam exercises on the ability to service Floating Semen Padang Volleyball Club athletes. Where the highest average score is found in push-up exercises